Analisis Kemampuan Siswa dalam Pemecahan Masalah Matematika Luas dan Keliling Bangun Datar di Sekolah Dasar: Analysis of Students' Ability in Solving Mathematical Problems of Area and Perimeter of Flat Shapes in Elementary School - Debby Yuliana Sinaga; Dinda Ayu Kristinasari; Kiki Fadilah Damanik; Leitary M Saragih; Rini Lestari; Sapna Kartika Putri; Suci Ayu Rahmada; Ulva Alvionita; Wulan Aulia Zahra (ITScience (Information Technology and Science), 2024)
Mathematics is a field of study that plays a vital role in various aspects of life. As an essential part of education, students are expected to have good mathematical abilities, including the ability to solve mathematical problems. However, they are less able to think critically when solving problems. This is supported by the finding that if the questions given are in the form of multiple choices, they are fully answered, while if the questions given are in the form of essays, many questions are not answered by students. This study uses a descriptive method with a qualitative approach. This research was conducted at SDN 124388 Pematangsiantar with a sample of 3 fifth-grade students. The data analysis technique in this study used various methods such as interviews, tests, observations, and documentation. Mathematical abilities in solving mathematical problems related to the area and circumference of flat shapes showed striking differences between SR, YN, and EFS students. SR students showed high mathematical abilities, YN had a moderate ability level, and EFS had low skills. This difference is reflected in the analysis of tests, interviews, and observations that the researcher has carried out. Students with high mathematical abilities master the problems in all three questions well. Students can systematically formulate problem-solving plans for the three questions. Students are careful in implementing problem-solving plans and re-checking the problem-solving steps for the three questions. Students classified as having moderate mathematical abilities can only master the problems in the three questions correctly while planning to problem-solve, implementing problem-solving plans, and re-checking the problem-solving steps are not yet able to be implemented so accurately.